Antifeedant and insecticidal activity of Polygonum persicaria extracts on Nomophila indistinctalis - Luisa Quesada-Romero; Carlos Fernández-Galleguillos; Jan Bergmann; Manuel A. Bravo; Eduardo Fuentes-Contreras (GarVal Editorial Ltda., 2017)
Context: Vegetal extracts represent an alternative to control against agricultural pests that have become resistant to pesticides. Using natural products is considered to be more friendly to the environment and safe. Aims: To determine the insecticidal and antifeedant activity of Polygonum persicaria extracts of two differents populations in Chile (Valparaiso and Curico) against Nomophila indistinctalis larvae. Methods: Insecticide Resistance Action Committee (IRAC) susceptibility test was used to evaluate the insecticidal activity of the extracts at concentrations of 100, 250, 500 and 1000 mg/L; against first instar larvae of Nomophila indistinctalis. The antifeedant activity was evaluated to determine the percentage of consumption in third instar larvae on treatment. Results: When comparing the control and the treatment groups in the antifeedant activity assay, significant differences (p<0.05) were observed after 90 minutes of exposure. With respect to the insecticidal activity, all extracts showed significant effects at the applied concentrations compared to the negative control. Moreover, the dichloromethane extracts of Curico and Valparaiso at concentrations greater than 500 mg/L showed a similar insecticidal activity as compared to the commercial formulation Neem. Conclusions: This work presents for the first time the results of the anti-feeding and insecticide activity of ethanol, methanol, and dichloromethane extracts from Polygonum persicaria on Nomophila indistinctalis. The results show that the extracts of this species can be used as an alternative for biological control. In addition, the results obtained allow a bioguided fractionation for the identification of secondary metabolites present in these extracts.